QUALIMETRY AS A TOOL FOR ASSESSING THE QUALITY OF EDUCATION (Pedagogy of Higher and Secondary Education, 2010)
The concept of qualimetry of education is examined in this article, classification of basic principles and its meaningfulness is proved in the evaluation of quality of education during preparation of modern specialists.
Keywords: qualimetry; quality; estimation; indexes; properties